Fiscal Decentralization and Economic Growth: Evidence from Selected Muslim Countries - Abd. Ghafar b. Ismail (Economic Journal of Emerging Markets, 2009)
Since 1970 era, the discussion about fiscal decentralization becomes an important subject. A recent World Bank study found that of the 75 developing and transition countries in the world with populations greater than 5 million, all but 12 claim to be embarked on some transfer of fiscal power from the central to sub national governments. This is a revolu-tion of how people think fiscally. The subject has also attracted many researchers to explore the decentralization system. As such many researchers mainly try to focus that fiscal decen-tralization would have a significant effect on economic growth. Empirically, these research-ers also prove that the decentralization approach of a nation's fiscal structure is an effective strategy to promote economic growth. The central structure of fiscal decentralization is the degree that creates growth-promoting decentralization systems that distinguish decentraliza-tion system capabilities in promoting economic growth to a greater or lesser degree. Hence, this paper will provide the empirical evidence for selected Muslim countries where these countries adopt the differences approaches in fiscal decentralization, i.e., transition coun-tries versus countries with a well-functioning fiscal system.